INSERTION OF INTRAUTERINE DEVICE (IUD) BY FAMILY AND COMMUNITY PHYSICIANS IN PRIMARY HEALTH CARE IN SANTA MARIA, RIO GRANDE DO SUL, BRAZIL - Carli, Luiz Felipe Dias; Bottari, Nathieli Bianchin; Konopka, Cristine Kolling; Jacobi, Luciane Flores (Seven Editora, 2026)
Unplanned pregnancy accounts for 40% of all pregnancies and remains a worldwide reality. Regarding physical health, the lack of reproductive planning to prevent unintended pregnancy is among the factors that worsen maternal mortality rates in Brazil. Therefore, guidance and access to contraceptive methods such as the intrauterine device (IUD) ensure women’s right to reproductive and sexual health care. The Intrauterine Device (IUD) is one of the highly effective and long-acting contraceptive methods offered by the Brazilian Unified Health System (SUS), although it is still underused. In this context, the present study aimed to expand IUD insertion among SUS users in the municipality of Santa Maria-RS within the primary health care network. Initially, a theoretical and practical training course on copper IUD insertion was provided to Family and Community Medicine resident physicians from the Universidade Federal de Santa Maria and Universidade Franciscana in order to increase the availability of IUDs in the municipality’s primary health care network. Subsequently, the IUD was offered as a contraceptive method to women during routine clinical consultations at Family Health Strategy (FHS) units. The project included 45 women aged 18 to 45 years who were SUS users in the city of Santa Maria, as well as four Family and Community Medicine physicians. The mean age of participants was 27 years, with 74.5% aged between 19 and 35 years; 42% had completed high school and 19.1% had completed higher education; 59.6% had paid employment; most were married and/or in a stable relationship (61.7%); and 72.3% had one or more previous pregnancies. The resident physicians who received training in Copper T 380A IUD insertion identified the following barriers before training: lack of prior knowledge and difficulty performing the procedure. After the training, 100% of the professionals reported feeling equipped with the necessary knowledge and skills, considering insertion to be an easy procedure. None of the 45 users experienced complications after IUD insertion. This study provided positive results that may support and encourage IUD insertion by Family and Community Medicine professionals, expanding the availability of long-acting contraception for the population.